2017
DOI: 10.3847/1538-4357/aa88b5
|View full text |Cite
|
Sign up to set email alerts
|

Non-local Thermodynamic Equilibrium Stellar Spectroscopy with 1D and 〈3D〉 Models. II. Chemical Properties of the Galactic Metal-poor Disk and the Halo

Abstract: From exploratory studies and theoretical expectations it is known that simplifying approximations in spectroscopic analysis (LTE, 1D) lead to systematic biases of stellar parameters and abundances. These biases depend strongly on surface gravity, temperature, and, in particular, for LTE vs. non-LTE (NLTE) on metallicity of the stars. Here we analyse the [Mg/Fe] and [Fe/H] plane of a sample of 326 stars, comparing LTE and NLTE results obtained using 1D hydrostatic models and averaged 3D models. We show that com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 69 publications
(83 reference statements)
4
37
0
Order By: Relevance
“…The four saturated lines (MgIb triplet: 5167.3, 5172.7, 5183.6, and 5528.4 Å) and the intermediate-strength line 5711.09 Å seem to reproduce the thin-thick disc sequences more precisely, also showing a decreasing trend in [Mg/Fe] even at supersolar metallicities. This is in agreement with the analysis of NLTE effects on Mg abundances done by Bergemann et al (2017), where they highlight the robust behaviour of the strong lines 5172, 5183, 5528, and 5711 Å. The higher dispersion present on the abundance results for the weak non-saturated lines with respect to the strong saturated ones is due to different factors.…”
Section: Disentangling the Thin And The Thick Disc Populationssupporting
confidence: 90%
See 2 more Smart Citations
“…The four saturated lines (MgIb triplet: 5167.3, 5172.7, 5183.6, and 5528.4 Å) and the intermediate-strength line 5711.09 Å seem to reproduce the thin-thick disc sequences more precisely, also showing a decreasing trend in [Mg/Fe] even at supersolar metallicities. This is in agreement with the analysis of NLTE effects on Mg abundances done by Bergemann et al (2017), where they highlight the robust behaviour of the strong lines 5172, 5183, 5528, and 5711 Å. The higher dispersion present on the abundance results for the weak non-saturated lines with respect to the strong saturated ones is due to different factors.…”
Section: Disentangling the Thin And The Thick Disc Populationssupporting
confidence: 90%
“…The selected lines in Table 1 have been widely used in the literature to determine both [Mg/Fe] and [α/Fe] abundances. Bergemann et al (2014Bergemann et al ( , 2017 analysed different approximations for radiative transfer and spectral line formation in model atmospheres, focused on their effect on Mg abundance determination using lines in the optical and infrared, among which there are four lines used in our analysis (5172, 5183, 5528, and 5711 Å). They find no significant differences between 1D LTE and 1D NLTE abundances, and for the lines in common with ours, they present a quite robust behaviour with respect to the full 3D NLTE calculations in cool FGK stars.…”
Section: Selected Mg I Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a comprehensive model atom based on accurate collisional data, Osorio & Barklem (2016) calculated departure coefficients for the Mg i levels and LTE and NLTE equivalent widths for the Mg i lines in a grid of the MARCS atmospheric models (Gustafsson et al 2008). The magnesium NLTE abundances of extended samples of cool stars were determined by Andrievsky et al (2010) and Bergemann et al (2017b). Taking advantage of the NLTE line formation for not only Mg i but also Fe i-Fe ii, Zhao et al (2016) and Mashonkina et al (2017) showed that the Galactic dwarf and giant stars at [Fe/H] ≤ −0.8 and the very metal-poor ([Fe/H] < −2) giants in the classical dwarf spheroidal galaxies Sculptor, Ursa Minor, Sextans, and Fornax reveal a similar plateau at [Mg/Fe] ≃ 0.3.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative interpretation of stellar spectra relies on the existence and accuracy of atomic data such as wavelengths, transition probabilities, energy levels, and hyperfine structure constants. Well-defined linelists with reliable and consistent atomic data are also very important for the analysis of deviations from local thermodynamic equilibrium (non-LTE effects) when modelling stellar atmospheres [15][16][17][18]. Together with realistic stellar models and high-resolution stellar spectra, accurate atomic and molecular data are essential to obtain chemical abundances with the level of accuracy needed by Galactic Surveys (Figure 4).…”
Section: Our Laboratory Measurementsmentioning
confidence: 99%